RECONSTRUCTING TOLERANCE IN EVERYDAY LIFE FOR YOUNG MUSLIMS TOWARDS INTERRELIGIOUS HARMONY - Achmad Faesol (Al'Adalah, 2022)
The level of tolerance towards non-Muslims among young Muslims today is concerning. It is because their views on religious differences have the potential to cause religious conflict. One of the studies shows that the campus as an educational institution has yet to construct conditions of religious tolerance intensively. This article examines the social construction of views on religious tolerance among educated Muslim youths using social construction analysis by Peter L. Berger and Thomas Luckman. The study results show that their intolerant views of non-Muslims are influenced by their social media, films, schoolteachers, community, and relationships. Most are worried and afraid that their faith (aqidah) will be interfered with or accused if they visit houses of worship of other religions. Some think that the visit is forbidden (haram). After the dialectical process of subjective, symbolic, and objective reality through FGDs, discussions with adherents of other religions, visits to churches, and others, they have a new understanding of religious moderation. Thus, the reconstruction effort strengthens inter-religious harmony in everyday life.